Inositol Metabolism in Plants. IV. Biosynthesis of Apiose in Lemna and Petroselinum - Roberts, R. M. (1967)
The biosynthesis of apiose was investigated in cell wall polysaccharide of Lemna gibba G3 (duckweed) and in detached leaves of Petroselinum crispum (parsley). Lemna grown either in short days or in continuous light incorporated (14)C from a medium containing myo-inositol-2-(14)C into d-apiosyl and d-xylosyl units of cell wall polysaccharides. Labeled d-apiose was characterized by paper chromatography, by formation of labeled crystalline di-O-isopropylidene d-apiose, and by gas chromatography of trimethylsilyl derivatives of apiose and of its sodium borohydride reduction product, apiitol. Periodate oxidation of labeled apiose revealed 86 to 94% of the (14)C was located in formaldehyde fragments corresponding to C3′ and C4. Comparison of this result with work reported by Grisebach and Doebereiner and by Beck and Kandler supports the conclusion that myo-inositol-2-(14)C was converted to d-apiose labeled specifically at C4. When l-arabinose-l-(14)C was supplied to Lemna, both l-arabinosyl and d-xylosyl units of cell wall polysaccharides became labeled, but no (14)C was found in d-apiose. Analysis of the medium external to the plants revealed the presence of a polysaccharide-like polymer that also contained labeled xylose and arabinose. Petroselinum leaves utilized myo-inositol-2-(3)H for the synthesis of apiose in apiin. These results provide direct evidence for a pathway of apiose biosynthesis involving d-glucuronic acid metabolism.